Respuesta :

Answer:

  -17

Step-by-step explanation:

Each term in the sequence is 5 less than the one before, so the first 4 terms are ...

  -2, -7, -12, -17

The 4th term of the sequence is -17.

__

The general term (an) of the sequence can be written as ...

  an = a1 +d(n -1)

where a1 is the first term and d is the common difference. Here, those are ...

  a1 = -2, d = -5

so the general term is ...

  an = -2 -5(n -1)

We can use this to find the 4th term:

  a4 = -2 -5(4 -3)

  a4 = -17